The message of John's letters living in the love of God - Jackman, David (Leicester, UK IVP, 1988)
Includes bibliographical references.
"The Bible Speaks today series has been placed in the Emmaus Bible College library in memory of Gordon W. Craig, 1926-1990".
Keywords: Bible. N.T. Epistles of John -- commentaries